Consumption Of Dates in Adolescent Increase Hemoglobin Levels (JURNAL IBU DAN ANAK, 2022)
Low levels of hemoglobin in the blood will have several effects, one of which is anemia. Around 25.1% of adolescents in Riau are suffer from anemia. Dates are an alternative that can be used to increase hemoglobin levels. Dates have several important components that can increase hemoglobin levels. The purpose of this study was to determine the effect of dates on the hemoglobin levels of female adolescents in Tahfiz Al-Yusra House, Pekanbaru City. The research design was Pre- Experimental with One Group Pretest-Posttest Design. This research was conducted at the Tahfiz Al-Yusra House, Pekanbaru City in January - May 2021. The sample in this study was 17 female adolescent aged 18-21 years who were taken using the total sampling technique. Collecting data using an observation sheet and measuring hemoglobin levels using a digital Hb tool. Dates intervention was given as much as 100 grams a day for 7 days. This study used the Dependent T test with a confidence degree of 95%, the average result of female adolescent hemoglobin levels before being given dates was 13.047 (SD = 0.6929) and after being given dates was 13.618 (SD = 0.8293). Based on the results of statistical testsshowed that there was a significant effect between dates on the hemoglobin levels of adolescent girls (P=0.002). It is recommended the educational institutions provide education on the importance of preventing anemia or advise adolescent, especially girls, to consume dates one for a day to help preven adolescent girl from experiencing anemia.